الأسلوب التفسيري للإمام المظهري في تفسير آيات الأحكام: Qazi Sanaullah Panipatti and his style & approach in his exegesis in the interpretation of Quranic injunctions - Dr.Hafiz Haris Saleem; Dr. Ghulam Hussain (Al Manhal Research Journal, 2023)
Qazi Sanaullah Panipatti is one of the most prominent and great scholar of the Islamic world. He is particularly known as a scholar of Qur'ān and Tafsīr in the Sub-continent. He has written many books in which the Tafsir Mazhari is very popular – A comprehensive exegesis of the Holy Qur'ān. This article carries out a comprehensive study of his Tafsīr and his methodology and style in the verses related to injunctions. The book is most celebrated Qur'ānic commentary in the Sub-continent. This article presents the methods, approach and worth of this book along with his biography. The method used in this research is descriptive and analytical. The study found that his writing style was unique and comprehensive. He has derived many solutions of contemporary issues from the perspective of the Holy Qur'ān. The study also recognized him as a socio- religious scholar for his time. At the end, the researcher has drawn some findings and conclusions.